Congenital anomalies of the coronary arteries - Silva, Andreia (2018)
Congenital coronary artery anomalies are modifications of their origin, course or structure and its incidence varies between 0,2 and 5,6% of the general population. Although the majority is asymptomatic, they are the second leading cause of sudden cardiac death in young athletes. The aim of this study is to highlight the main anomalies with hemodynamic significance, including the anomalous origin of a coronary artery from the opposite sinus and anomalous origin of the left coronary artery from pulmonary artery. The anomalous aortic origin of a coronary artery from the opposite sinus accounts for 14-16% of all cardiac deaths, that unexpectedly occur in healthy children or young athletes during or immediately after exercise. The mechanism responsible for the compression/occlusion of the coronary artery originating from the opposite sinus is still unclear and there are several proposed mechanisms. The clinical presentation of these patients is variable and physical examination is normal in most individuals. Transthoracic echocardiogram is the diagnostic test most commonly used. Treatment and management are controversial topic. The anomalous origin of the left coronary artery from pulmonary artery is a very rare condition and without surgery, most infants die within the first 12 months of life. The echocardiogram is also the method of choice for diagnostic confirmation. The diagnosis of this congenital anomaly in an infant, usually seriously ill, is an indication for urgent surgery. Because these anomalies produce hemodynamic changes, it is important an early diagnosis and treatment.